(untitled) (Biodiversitas Journal of Biological Diversity, 2009)
Perwitasari-Farajallah D, Kyes RC, Iskandar E (2010) Microsatellite DNA polymorphisms for colony management of long-tailed macaques (Macaca fascicularis) population on the Tinjil Island. Biodiversitas 11: 55-58. Polymorphic genetic markers are the basic requirement for studies on population and conservation genetics of non-human primates. In this paper, we screened microsatellites for their polymorphism and gene typing of DNA samples from blood of wild long-tailed macaques (Macaca fascicularis) from Tinjil Island population. Among the three primer sets tested, two are polymorphic. They were D1S548 and D3S1768. Average observed heterozygosity (Ä¤) within populations ranged between 0.264-0.555. D1S1768 locus was highly polymorphic and 24 alleles were detected among two loci. Estimation of genetic variability for the Tinjil population (Ä¤) was 0.485. The results obtained provide further insight into the long-term viability of the population and help in creating genetic management of both captive and natural habitat breeding colonies of primates. Key words: microsatellite, variations, social groups, long-tailed macaques, Macaca fascicularis